Hydrogen sensing performance of a Pd/HfO2/GaOx/GaN based metal-oxide-semiconductor type Schottky diode. (18th October 2018) - Chang, Ching-Hong; Lin, Kun-Wei; Lu, Hsin-Hau; Liu, Rong-Chau; Liu, Wen-Chau
Abstract: An interesting hydrogen sensor based on a Pd/HfO2 /GaOx /GaN metal-oxide-semiconductor (MOS) structure is fabricated and demonstrated. The HfO2 and GaOx layers are prepared using a sputtering approach and hydrogen peroxide (H2 O2 ) treatment. The hydrogen sensing characteristics of the studied device are comprehensively studied. Experimentally, good hydrogen sensing characteristics, including a high sensing response of 8.47 × 10 5, a low detection level of 5 ppm H2 /air, and reversible, short response and recovery times upon exposure to different hydrogen concentrations and temperatures are obtained. The influence of humidity on hydrogen sensing performance is also studied. The exothermic action of the hydrogen adsorption process leads to a decreased hydrogen sensing response at higher temperatures. Consequently, the studied Pd/HfO2 /GaOx /GaN MOS diode is promising for high-performance hydrogen sensing applications and integration with other GaN-based high-speed devices on a chip. Graphical abstract: A high-performance hydrogen gas sensor has been prepared based on a Pd/HfO2 /GaOx /GaN metal-oxide-semiconductor (MOS)-type Schottky diode. Highlights: A high-performance Pd/HfO2 /GaOx /GaN MOS-type hydrogen sensor was fabricated. The H2 O2 treatment was used to grow the GaOx dielectric layer. The lowest detection level was 5 ppm H2 /air. The hydrogen sensing characteristics were comprehensively studied. The influence of humidity on hydrogen sensing performance was also studied.